1978
DOI: 10.1136/gut.19.5.396
|View full text |Cite
|
Sign up to set email alerts
|

Transmucosal potential difference; diagnostic value in gastro-oseophageal reflux.

Abstract: SUMMARY Nineteen patients with symptoms of upper gastrointestinal disease were assessed by endoscopy. Transmucosal potential difference (PD) in the lower oesophagus was recorded and suction biopsy specimens were obtained from the site of measurement and examined by light microscopy after haematoxylin and eosin staining. In 10 patients with normal histology, mean PD was -14-4 mV (SEM + 0-4 mV), whereas in nine patients with histological changes of reflux mean was + 9.4 mV (SEM ± 3 0 mV). In this latter group, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

1980
1980
1995
1995

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 10 publications
(12 reference statements)
0
9
0
1
Order By: Relevance
“…In the stomach measurements of transmural electrical potential differences have been shown to detect damage to the gastric mucosal barrier [2,4,8,9,10,13,22], which led to the conclusion that maintenance of gastric PD is a sensitive indicator of mucosal integrity [5,6,20]. More recently it has been suggested that, similar to the stomach, transmural potential difference measurements of the esophagus represent an accurate method for the diagnosis of esophageal mucosal damage [17]. More recently it has been suggested that, similar to the stomach, transmural potential difference measurements of the esophagus represent an accurate method for the diagnosis of esophageal mucosal damage [17].…”
Section: Sehliisselwiirter: Gastro6sophagealer Reflux -Potentialdiffementioning
confidence: 99%
“…In the stomach measurements of transmural electrical potential differences have been shown to detect damage to the gastric mucosal barrier [2,4,8,9,10,13,22], which led to the conclusion that maintenance of gastric PD is a sensitive indicator of mucosal integrity [5,6,20]. More recently it has been suggested that, similar to the stomach, transmural potential difference measurements of the esophagus represent an accurate method for the diagnosis of esophageal mucosal damage [17]. More recently it has been suggested that, similar to the stomach, transmural potential difference measurements of the esophagus represent an accurate method for the diagnosis of esophageal mucosal damage [17].…”
Section: Sehliisselwiirter: Gastro6sophagealer Reflux -Potentialdiffementioning
confidence: 99%
“…The measurement of buccal [19. 20], esophageal [21,22], small intestinal [24], colonic [25] and rectal [26] PD was indeed described as both a research and diagnostic tool.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have measured transmucosal esophageal PD in patients with reflux esophagitis [21][22][23][24][25][26][27], Many of them found less negative PD values in patients with reflux esophagitis compared with healthy subjects, although two studies [22,25] reported higher (i.e. more negative) values (table 1).…”
Section: Esophageal Pd In Esophageal Diseasementioning
confidence: 99%
“…However, more recent studies [21][22][23][24][25][26][27], 52 Scarpignato/Micali/Galmiche Transmucosal Potential Difference asan Index of Esophageal Mucosal Integrity [31], Four years later, the same team [23] reported a further refinement of the technique by introducing the Ringer washout of the esophagus in order to prevent or reduce the interference of junction, diffusion and/or streaming potential (see below).…”
Section: Esophageal Pdmentioning
confidence: 99%